2015
DOI: 10.1111/j.1728-4465.2015.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Unmet Need for Family Planning in the Postpartum Period

Abstract: Despite renewed interest in postpartum family planning programs, the question of the time at which women should be expected to start contraception after a birth remains unanswered. Three indicators of postpartum unmet need consider women to be fully exposed to the risk of pregnancy at different times: right after delivery (prospective indicator), after six months of amenorrhea (intermediate indicator), and at the end of amenorrhea (classic indicator). DHS data from 57 countries in 2005-13 indicate that 62 perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
87
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 11 publications
0
87
0
6
Order By: Relevance
“…Yet the opportunity is often missed. Data from 57 low‐ and middle‐income countries demonstrated that 62% of women giving birth in the preceding year did not initiate contraception immediately postpartum . Even in high‐income countries, provision of effective contraception after delivery is often sub‐optimal.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the opportunity is often missed. Data from 57 low‐ and middle‐income countries demonstrated that 62% of women giving birth in the preceding year did not initiate contraception immediately postpartum . Even in high‐income countries, provision of effective contraception after delivery is often sub‐optimal.…”
Section: Introductionmentioning
confidence: 99%
“…During the year following the birth of a child, 40% of women are estimated to have an unmet need for contraception [2]. Fewer than 50% of women in 30 of the 43 countries with recent Demographic and Health Surveys (DHS) used any method of contraception during 9-11 months postpartum, and in 12 of these countries the use was below 20% [3].…”
Section: Introductionmentioning
confidence: 99%
“… De facto LAM use (women protected by LAM but not declaring it as a method) could be integrated into the present analysis as another traditional method as many women give breastfeeding or amenorrhea as reasons for not using modern contraception in sub‐Saharan Africa (Sedgh and Hussein ), but these women also overwhelmingly abstain postpartum (Rossier et al. ), and thus are mostly already accounted for.…”
mentioning
confidence: 99%